DEVELOPMENT OF UPBRINGING, SCHOOLS, AND PEDAGOGICAL THOUGHT IN MAVAROUNNAHR FROM THE SECOND HALF OF THE 14TH CENTURY TO THE 16TH CENTURY - Sultonova , Nafisa (Journal of Pedagogical and Philological Research, 2026)
This article provides a historical-pedagogical analysis of the formation and development of the education and upbringing system in the territory of Mavarounnahr during the second half of the 14th to the 16th centuries. It highlights the state-level attention given to enlightenment during the reigns of Amir Temur, the Timurids, and the Shaybanids. The role of schools (maktabs) and madrasas in education, as well as their activities, are demonstrated based on historical facts. The development of the scientific environment and educational content during the era of Mirzo Ulugbek is analyzed. Special attention is paid to Alisher Navoi’s pedagogical views on the upbringing of a "perfect human." The continuation of educational traditions during the Shaybanid period in the 16th century is also explored. The article summarizes the developmental stages of pedagogical thought, and the research findings hold theoretical significance for the modern education system.